2021
DOI: 10.1109/tpel.2020.3024862
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities, Challenges, and Potential Solutions in the Application of Fast-Switching SiC Power Devices and Converters

Abstract: Power devices based on wide-bandgap (WBG) material such as silicon-carbide (SiC) can operate at higher switching speeds, higher voltages and higher temperatures compared to those based on silicon (Si) material. This paper highlights some opportunities brought by SiC devices in existing and emerging applications in terms of efficiency and power density improvement. While the opportunities are clear, there are also design challenges that must be met in order to realize their full potential. For example, the fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 111 publications
0
36
0
Order By: Relevance
“…The negative impact of fast-switching WBG devices and inverters has drawn significant attention with the increasing adoption of WBG devices in various motor drive applications, such as electric vehicles [16]. The overvoltage due to the reflected wave phenomenon with GaN HEMTs, SiC MOSFETs and Si MOSFETs are studied and compared in [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative impact of fast-switching WBG devices and inverters has drawn significant attention with the increasing adoption of WBG devices in various motor drive applications, such as electric vehicles [16]. The overvoltage due to the reflected wave phenomenon with GaN HEMTs, SiC MOSFETs and Si MOSFETs are studied and compared in [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that when the rising/falling time of the inverter output voltage is four times of the voltage wave propagation time along the cable, the motor terminal overvoltage can be fully attenuated. Multilevel converters can also be used to attenuate the motor terminal overvoltage since there are more steps in the output voltage, hence less dv/dt [16]. The amplitude of the voltage overshoot at the motor terminal is proportional to the voltage change (ΔV) of the inverter output voltage, where multilevel converters have a lower voltage change (ΔV), hence can attenuate the motor terminal overvoltage.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages of WBG devices and their decreasing cost, it should be noted that they are still more expensive than conventional semiconductors [44]. The most developed and widespread WBG devices are those using gallium nitride (GaN) [45][46][47][48] and silicon carbide (SiC) [32,44,[49][50][51][52] semiconductors. These two types of WBG devices are becoming increasingly popular in the field of EVs due to their higher blocking voltage, frequency, and operation temperature [53,54].…”
Section: Wide-bandgap Semiconductorsmentioning
confidence: 99%
“…IDE-BANDGAP (WBG) power devices developed over the past decades, such as silicon carbide (SiC) and gallium nitride (GaN) devices, offer new opportunities pushing the boundaries of power converter performances [1]. Alongside the development of power devices, multilevel converter topologies have also been an extensively studied topic since the 1960s, from the well-known neutral point clamped (NPC) converters, flying capacitor converters and cascaded H-bridge converters, to T-type converters, active-NPC (ANPC) converters and modular multilevel converters (MMC) [2], [3].…”
Section: Introductionmentioning
confidence: 99%